MODAL MENINGKATKAN HARGA SAHAM PERBANKAN DI INDONESIA - Sari, Laynita; Septiano, Renil (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to determine the effect of capital on the sham price of banking companies in Indonesia. Capital is obtained from the company's financial statements and the company's share price is obtained from the  Indonesia Stock Exchange website. The research sample amounted to forty-five banking companies in Indonesia from 2020-2022, which were determined by the purposive sampling method. The type of data used is secondary data in the form of annual reports of banking companies for the 2020-2022 period and stock prices on the Indonesia Stock Exchange. The data analysis technique uses multiple linear regression analysis with the help of SPSS program version 27.0.  This research found that the amount of capital provides empirical evidence of positively influencing the share prices of banking companies listed on the Indonesia Stock Exchange in 2020-2022